Relations between human leukocyte antigens and autoimmune hepatitis in Turkish children - Seda GEYLANİ GÜLEÇ; Nafiye URGANCI; Tuğçin Bora POLAT; Emirzad DEMİREL; Erkan YILMAZ (Turkish Journal of Gastroenterology, 2019)
-